2017
DOI: 10.1038/s41598-017-08480-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise leads to unfavourable cardiac remodelling and enhanced metabolic homeostasis in obese mice with cardiac and skeletal muscle autophagy deficiency

Abstract: Autophagy is stimulated by exercise in several tissues; yet the role of skeletal and cardiac muscle-specific autophagy on the benefits of exercise training remains incompletely understood. Here, we determined the metabolic impact of exercise training in obese mice with cardiac and skeletal muscle disruption of the Autophagy related 7 gene (Atg7h&mKO). Muscle autophagy deficiency did not affect glucose clearance and exercise capacity in lean adult mice. High-fat diet in sedentary mice led to endoplasmic reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 61 publications
(61 reference statements)
2
28
0
Order By: Relevance
“…Moreover, we found that the expression of other key autophagy-related genes such as ULK1, Atg12, and Atg4B, was significantly upregulated at the protein level in the left ventricle of rats with exercise-induced myocardial hypertrophy, whereas SQSTM1 (a marker of reduced autophagy) was downregulated. The findings are in concordance with previous results demonstrating that autophagy is enhanced by exercise training Yan et al, 2017;Li et al, 2019;Moradi et al, 2019), and endurance exercise provided cardioprotective effect by upregulating autophagy (Lee et al, 2017). Consistently, a highly activated autophagy was also observed in IGF-1 induced cardiomyocyte hypertrophy, which was agreed with that IGF-1 inhibition attenuated autophagosome formation (Renna et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we found that the expression of other key autophagy-related genes such as ULK1, Atg12, and Atg4B, was significantly upregulated at the protein level in the left ventricle of rats with exercise-induced myocardial hypertrophy, whereas SQSTM1 (a marker of reduced autophagy) was downregulated. The findings are in concordance with previous results demonstrating that autophagy is enhanced by exercise training Yan et al, 2017;Li et al, 2019;Moradi et al, 2019), and endurance exercise provided cardioprotective effect by upregulating autophagy (Lee et al, 2017). Consistently, a highly activated autophagy was also observed in IGF-1 induced cardiomyocyte hypertrophy, which was agreed with that IGF-1 inhibition attenuated autophagosome formation (Renna et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…High‐fat feeding results in an overload of lipids that drives lipid oxidation without high energy demands, putting stress on mitochondrial metabolism . High‐fat feeding in mice with a skeletal muscle knockout of Atg7, an autophagy machinery protein, impaired mitochondrial function, further supporting the role of autophagy in preserving mitochondrial function during metabolic stress. In our study, both WT and Bcl2 AAA mice had improved mitochondrial lipid oxidation capacity after high‐fat feeding, despite glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagic proteins may fail to be properly translocated during excessive exercise, e.g., damaged mitochondria and misfolded proteins, which leads to the reduction of autophagic efficiency [6,12]. Yan, et al [35] have reported that maintaining a normal level of autophagy during exercise is essential to cardiac metabolism and cardioprotection. Our results show that the EEP group has high-intensity exerciselike autophagic induction, despite the decreased expression of p62 and the increased ratio of LC3II/ LC3I.…”
Section: Exercise Preconditioning Induces Autophagy By Intermittent Mmentioning
confidence: 99%